Secondhand Smoking and the Risk of Esophageal Squamous Cell Carcinoma in a High Incidence Region, Kashmir, India: A Case-control–observational Study. Issue 1 (January 2016) - Rafiq, Rumaisa; Shah, Idrees Ayoub; Bhat, Gulzar Ahmad; Lone, Mohd Maqbool; Islami, Farhad; Boffetta, Paolo; Dar, Nazir Ahmad
Abstract : Abstract: Studies have associated secondhand smoking (SHS) with cancers of the lung, larynx, and pharynx. Only a few studies have examined the association between SHS and esophageal squamous cell carcinoma (ESCC) and the findings are inconclusive. We aimed to investigate the association between SHS and risk of ESCC in a case-control study in Kashmir, where the incidence of ESCC is high. We recruited 703 histopathologically confirmed ESCC cases and 1664 hospital-based controls individually matched to the cases for age, sex, and district of residence. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated using conditional logistic regression models. Among never-tobacco users, the ORs for the association between SHS and ESCC risk were above unity with ever exposure to SHS (OR = 1.32; 95% CI, 0.43–4.02) and exposure to SHS for >14 h/wk (median value) (OR = 2.69; 95% CI, 0.75–20.65). In the analysis of data from all participants, the OR (95% CI) for the association between SHS and ESCC was (OR = 1.02; 95% CI, 0.53–1.93) for SHS ⩽14 h/wk and (OR = 1.91; 95% CI, 0.75–4.89) for SHS >14 h/wk in the models adjusted for tobacco use and several other potential confounding factors. We found an indication of increased risk of ESCC associated with exposure to SHS. Studies with larger numbers of SHS-exposed never tobacco users are required to further examine this association. Abstract : Supplemental Digital Content is available in the text